The histocompatibility antigen in asbestos related disease. Issue 12 (December 1992) - Al Jarad, N; Uthayakumar, S; Buckland, E J; Green, T S; Ord, J; Newland, A C; Rudd, R M
Abstract : Thirty nine phenotypes of human leucocyte antigens (HLA)-A-B-DR and DQ were obtained from 99 asbestos workers (one woman and 98 men). Presence or absence of antinuclear antibodies and rheumatoid factor was determined in 91 of them. Workers were divided into five groups: asbestos workers with no apparent disease (AW; n = 17), diffuse benign pleural disease (PD; n = 31), asbestosis (AS; n = 24), asbestosis with lung cancer (AS-CA; n = 14), and mesothelioma (M; n = 13). Compared with AW, several trends of differences of HLA antigen prevalence were found in patients with asbestos related disease, but these did not achieve statistical significance when p was corrected (pcorr) by number of analyses undertaken. Analysis of the results obtained in previous studies together with the results of this study showed that compared with AW, AS patients had decreased prevalence of HLA-DR5 (pcorr < 0.02). Reasons for the differences in results of previous studies and statistical methods commonly used to compare prevalences of HLA antigen are discussed.